Patient Demographics and Drug Prescription Pattern among Hypertensive Patients of Pokhara Valley - Khan, GM; Thapa, RK; Khakurel, A; Shrestha, G; Katila, N; Bhurtel, S; Thapa, P; Parajuli, K (Journal of Chitwan Medical College, 2013)
Hypertension is a common disease of the present world. Patient characteristics and use of anti-hypertensive agents directly affect the development and control of hypertension respectively. So, the objective of this study was to determine the patient demographics and drug prescription pattern among hypertensive patients of Pokhara valley. A community based descriptive cross-sectional study was conducted in different places of Pokhara valley. Performa was used for the collection of data and analysis was done using MS-excel and SPSS (version 17.0). The study showed that majority of the hypertensive patients were males of Brahmin and Newar community with susceptible age group of 60-69 years. Majority of the patients were non-vegeterian, non-alcoholic and non-smoker. The anti-hypertensive prescription pattern revealed that 80% of the patients were on monotherapy and calcium channel blockers were the mostly prescribed medication. Prescription of anti-hypertensive agents along with other medications for concomitant diseases was also observed. The prescription pattern was found to be rational and should be regularly monitored. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8440 Journal of Chitwan Medical College Vol.3(2) 2013 32-35